(untitled) (Journal of Health Management and Pharmacy Exploration, 2026)
The use of facial whitening creams among adolescent girls is often carried out without adequate understanding of the active ingredients contained in the products, including the risks of hazardous substances such as mercury and hydroquinone. Lack of attention to cosmetic product legality has contributed to the widespread use of products without official distribution permits. This research was conducted to examine the levels of knowledge and attitudes related to the practice of using whitening cream among female students at SMA Negeri 1 Binongko. This research employed a quantitative observational method with a descriptive analytic approach and a cross-sectional design. The sampling technique used was purposive sampling based on predetermined inclusion criteria. The sample consisted of 56 students calculated using the Slovin formula. Data were collected through a structured questionnaire that had been tested for validity using Pearson correlation and reliability using Cronbach’s Alpha. Data were processed using chi-square analysis with SPSS version 27 software. The results showed that most respondents had a low level of knowledge (76.8%), but demonstrated high positive attitudes (87.5%) and good practices in using whitening cream (76.8%). The chi-square test indicated no significant relationship between knowledge and practice (p = 0.989), while a significant relationship was found between attitude and practice (p = 0.001). This study suggests the need for continuous educational programs in schools to enhance adolescents’ awareness of the importance of choosing safe and legally registered cosmetic products. Further research is recommended to explore additional factors such as social media influence, family roles, and psychological aspects in decision-making related to cosmetic use.